Offspring school performance at age 12 after induction of labor vs non‐intervention at term: A linked cohort study. (22nd February 2023) - Burger, Renée J.; Mol, Ben W.; Ganzevoort, Wessel; Gordijn, Sanne J.; Pajkrt, Eva; Van Der Post, Joris A. M.; De Groot, Christianne J. M.; Ravelli, Anita C. J.
Abstract: Introduction: The incidence of induction of labor, for both medical reasons and as an elective procedure, has been rising and a further increase in induction of labor following the ARRIVE trial may be expected. The effects of induction of labor at term on childhood neurodevelopment, however, are not well studied. We aimed to study the influence of elective induction of labor for each week of gestation separately from 37 to 42 weeks on offspring school performance at 12 years of age after uncomplicated pregnancies. Material and methods: We performed a population‐based study among 226 684 liveborn children from uncomplicated singleton pregnancies, born from 37 +0 to 42 +0  weeks of gestation in cephalic presentation in 2003–2008 (no hypertensive disorders, diabetes or birthweight ≤p5) in the Netherlands. Children with congenital anomalies, of non‐white mothers and born after planned cesarean section were excluded. Birth records were linked with national data on school achievement. We compared, using a fetus‐at‐risk approach and per week of gestation, school performance score and secondary school level at age 12 in those born after induction of labor to those born after non‐intervention, ie spontaneous onset of labor in the same week plus all those born at later gestations. Education scores were standardized to a mean of 0 and a standard deviation of 1 and adjusted in the regression analyses. Results: For each gestational age up to 41 weeks, induction of labor was associated with decreased school performance scores compared with non‐intervention (at 37 weeks −0.05 SD, 95% confidence interval [CI] −0.10 to −0.01 SD; adjusted for confounding factors). After induction of labor, fewer children reached higher secondary school level (at 38 weeks 48% vs 54%; adjusted odds ratio [aOR] 0.88, 95% CI 0.82–0.94). Conclusions: In women with uncomplicated pregnancies at term, consistently, at every week of gestation from 37 to 41 weeks, induction of labor is associated with lower offspring school performance at age 12 and lower secondary school level compared with non‐intervention, although residual confounding may remain. These long‐term effects of induction of labor should be incorporated in counseling and decision making. Abstract : Induction of labor at term is associated with reduced offspring school performance compared with non‐intervention in uncomplicated pregnancies at every week from 37 to 41 weeks. Children are 10% less likely to reach higher secondary school level following elective induction.